2007
DOI: 10.1080/00986280701498558
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it Short and Sweet: Brief, Ungraded Writing Assignments Facilitate Learning

Abstract: Can short, ungraded, free-writing assignments promote learning of course material? We randomly assigned introductory psychology recitation sections (N = 978 students) to writing or thinking conditions. For all sections, teaching assistants presented students with a discussion topic based in current coursework. Students either wrote or thought about the topic for 5 min. All sections then discussed the topic for approximately 10 min. Exams included questions related to the discussion topics. Students in the writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 14 publications
2
45
0
1
Order By: Relevance
“…Most have shown significant effects of writing on learning (Atasoy, 2013;Drabick, Weisberg, Paul & Bubier, 2007;Gingerich et al, 2014;Yildiz, 2012); at the same time, some studies have shown null or limited effects (e.g., Linton et al, 2014;Spirgel & Delaney, online 2014;Yassin & Yong, 2013). Researchers have measured the effects of writing on learning in varied ways, over both short time scales such as the particular writing activity, and longer time scales such as the unit of study or the academic year (Correnti, Matsumura, Hamilton & Wang, 2012;Schumacher & Nash, 1991;Tomas & Richie, 2014).…”
Section: Recent Progress In the Methodology Of Writing To Learnmentioning
confidence: 99%
“…Most have shown significant effects of writing on learning (Atasoy, 2013;Drabick, Weisberg, Paul & Bubier, 2007;Gingerich et al, 2014;Yildiz, 2012); at the same time, some studies have shown null or limited effects (e.g., Linton et al, 2014;Spirgel & Delaney, online 2014;Yassin & Yong, 2013). Researchers have measured the effects of writing on learning in varied ways, over both short time scales such as the particular writing activity, and longer time scales such as the unit of study or the academic year (Correnti, Matsumura, Hamilton & Wang, 2012;Schumacher & Nash, 1991;Tomas & Richie, 2014).…”
Section: Recent Progress In the Methodology Of Writing To Learnmentioning
confidence: 99%
“…There is extensive data showing that writing is good for students (e.g. Drabick et al, 2007;Marek et al, 2005;Nevid, Pastva & McCelland, 2012;Stewart et al, 2010). More specifically, Angelo (1995) and others (Blake, 2005;Dunn & Smith, 2008;Mills, 2008;O'Connell & Dyment, 2006;Tsui, 1999;2002;Wade, 1995) all contend that writing positively impacts student learning, ability to think critically and ability to reflect on course material.…”
Section: Control Beliefs N Easymentioning
confidence: 99%
“…This formative assessment tool gained further scholarly attention in subsequent decades, wherein it was advocated as encouraging active learning (Anderson & Burns, 2013;Cross & Angelo, 1988;Holtzman, 2007;Wilson, 1986); highlighting emotional reactions to and understanding of learning material (Chizmar & Ostrosky, 1998;Drabick, Weisberg, Paul, & Bubier, 2007;Kloss, 1993); and strengthening student-faculty engagement (Lucas, 2010;Wilson, 1986). A major part of its appeal can be attributed to its low-tech nature and its adaptability to different subjects and situations.…”
Section: Minute Papermentioning
confidence: 99%